Trends in socioeconomic health inequalities in the Netherlands, 1981–1999 - Dalstra, J (BMJ Group, 2002)
Study objective: To determine changes in socioeconomic inequalities in self reported health in both the 1980s and the 1990s in the Netherlands. Design: Analysis of trends in socioeconomic health inequalities during the last decades of the 20th century were made using data from the Health Interview Survey (Nethhis) and the subsequent Permanent Survey on Living Conditions (POLS) from Statistics Netherlands. Socioeconomic inequalities in self assessed health, short-term disabilities during the past 14 days, long term health problems and chronic diseases were studied in relation to both educational level and household income. Trends from 1981 to 1999 were studied using summary indices for both the relative and absolute size of socioeconomic inequalities in health. Setting: The Netherlands. Participants: For the period 1981–1999 per year a random sample of about 7000 respondents of 18 years and older from the non-institutionalised population. Main results: Socioeconomic inequalities in self assessed health showed a fairly consistent increase over time. Socioeconomic inequalities in the other health indicators were more or less stable over time. In no case did socioeconomic inequalities in health seemed to have decreased over time. Socioeconomic inequalities in self assessed health increased both in the 1980s and the 1990s. This increase was more pronounced for income (as compared with education) and for women (as compared with men). Conclusion: There are several possible explanations for the fact that, in addition to stable health inequalities in general, income related inequalities in some health indicators increased in the Netherlands, especially in the early 1990s. Most influential were perhaps selection effects, related to changing labour market policies in the Netherlands. The fact that the health inequalities did not decrease over recent years underscores the necessity of policies that explicitly aim to tackle these inequalities.